The Analysis of School Health Development Index (SDHI) (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
The grand strategy of the Ministry of Health is the proper functioning of evidence-based health information systems through basic data and indicators. Therefore, this study aims at formulating an analysis of the needs, dimensions and indicators of School Health Development Index (SHDI). The samples included 50 schools for all units of educational levels in Buleleng Regency. The study employed the method of participant observation, documentation studies, interviews and questionnaires. Based on the results and discussion, it can be concluded that 1) Healthy school is a fixed price for every school, 2) The understanding of School Health Index Development (SHDI) of UKS supervising teachers in schools is still lacking, 3) the use of SHDI in every school is very important to measure the level or health status of each school in Buleleng Regency 4), The dimensions of SHDI are a) School policy, b) Work Program, c) Infrastructures, and d) School community behavior, 5) The existence of the SHDI guidebook becomes one of the bases for SHDI achievement.